2009 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2009
DOI: 10.1109/robio.2009.5420476
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation on the contact deformation distributionin a wire race ball bearing

Abstract: A mathematical model was firstly built for investigating the contact deformation distribution in a wire race ball bearing. The numerical computing program was developed in MATLAB ® , by employing an example of a wire race ball bearing with a 1000 mm diameter used in a large-scale caterpillar disaster relief robot. The contact deformation distribution in the elliptical contact zone of the wire and the ball was obtained. The finite element simulation was carried out to demonstrate the validity of the mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…At present, the domestic and foreign researchers on the contact fatigue and wear experiment of wire race ball bearing showed that friction and wear always happened in the whole process of balls contacting with the raceway; under the action of cyclic alternating contact stresses, the contact fatigue crack generated on the wire raceway, and formed pitting, and aggravated friction and wear between the contact surface; wear could change the geometry of contact surface, then change load transferring and the contact stress, as well as aggravate contact fatigue [7][8][9][10][11][12][13][14]. This paper takes wear as optimal design focus, and limits contact fatigue by controlling contact load in the form of the constraint at the same time, to extend bearing's life.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the domestic and foreign researchers on the contact fatigue and wear experiment of wire race ball bearing showed that friction and wear always happened in the whole process of balls contacting with the raceway; under the action of cyclic alternating contact stresses, the contact fatigue crack generated on the wire raceway, and formed pitting, and aggravated friction and wear between the contact surface; wear could change the geometry of contact surface, then change load transferring and the contact stress, as well as aggravate contact fatigue [7][8][9][10][11][12][13][14]. This paper takes wear as optimal design focus, and limits contact fatigue by controlling contact load in the form of the constraint at the same time, to extend bearing's life.…”
Section: Introductionmentioning
confidence: 99%